Voting after transition: Political preferences of Serbia’s transitional losers - Jović Nikola; Bursać Dejan (Filozofija i Društvo, 2025)
Economic crises create specific social conditions that affect voter preferences and behaviors. The Global Financial Crisis of 2007-2008 reached Serbia a year later, causing a major shock to the fragile Serbian economy, already burdened by the legacies of wars and international isolation during the 1990s, compounded by inequalities and uncertainties stemming from the delayed transition. Subsequent elections brought the collapse of the post-2000 political consensus, with many liberal and social democratic parties never recovering. This led to the domination of the populist Serbian Progressive Party (SNS) in the party system from there on. The main hypothesis of this article posits that the 2008 crisis solidified the pool of transitional losers composed of low skilled workers, the unemployed, low educated, rural populations, and elderly, providing continuous support for SNS ever since. The authors investigate whether the socioeconomic status of these groups still correlates with SNS votes, even though the party has been in power for 12 years. If the correlation stands, it implies that past economic traumas continue to influence voter preferences to this day. The study utilizes original data from two nationwide public opinion surveys.